Integration of a simulation platform into a business process management tool - Kanalıcı, İbrahim Halil. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
Information technology has already gone beyond being a supportive tool for businesses. Strong competition and increased costs force businesses act more efficiently and rapidly, so almost in every business, the operations are carried out in IT platforms where the processes are automated. These platforms are referred to as Business Process Management (BPM) Suites. With this motivation, most companies analyze and reengineer their workflows. At this point, it is vital to be able to monitor current or reengineered business processes with key performance indicators and keep the process flows under control. This introduces a challenge for the management to evaluate how any particular modification to any of the process workflows affects the performance measures. Therefore simulation becomes an essence in the contemporary management of businesses. In practice, major business process management softwares include some kind of simulation environment either as an embedded engine within the modeling component or through third-party integration. In this study a general purpose simulation platform is analyzed and a mapping algorithm is developed to integrate modeling capabilities of a BPM tool with this simulation environment.
Keywords: Industrial management -- Computer simulation.; Business planning.; Reengineering (Management).